Relationship between phosphorylation and synthesis of goldfish optic nerve proteins during regeneration - Larrivee, DC (J Neurosci, 1989)
After intraocular injection of radiolabeled phosphate and 3H-proline, the labeling of goldfish optic nerve proteins was monitored over a 7 week period of regeneration following a lesion to the optic tract. Labeled phosphate incorporation into total nerve protein increased to a peak value about twice that in normal nerve at 3 weeks after injury, then declined to slightly above normal by 7 weeks. Incorporation of 3H- proline showed a higher rise and a steeper decline, with values still significantly above normal at 7 weeks. Two-dimensional gel electrophoresis revealed that almost all the individual proteins examined underwent an increase in 3H-proline incorporation with a peak at about 3 weeks. However, only 4 proteins showed an increase in incorporation of 32P correlated with the increase in 3H-proline. The closest correlation was seen for protein 4, the equivalent of the growth-associated protein GAP-43; for the other 3 proteins (15, 31, and 38) 32P incorporation remained elevated even when 3H-proline incorporation had declined. Two other proteins (24e and 48) showed increased 32P incorporation not correlated with 3H-proline changes. Several proteins showed a decrease in 32P incorporation, even though 3H- proline incorporation was increased. For example, the phosphorylation of ON2, a neuronal intermediate filament protein, showed a long-lasting decline, which was already evident at 1 week and had not yet returned to normal by 7 weeks. Other proteins in this group (33, 37, and 46) showed a faster recovery.(ABSTRACT TRUNCATED AT 250 WORDS)